A mediação emocional na constituição de um grupo comunitário - Baptista, Rogério Rodolfo (2006)
The subject this research is the group with aim scrutiny the group process and this mediation in the consciosness in the people of the ONG inside one perifherical community in the inner paulist, to stand out your affective aspects. Sometimes mobilize action, sometimes to draw up and to make the group to go back. The affective aspects are happen in all social process in one community and the groups, because in these to take place the necessary condition to form the mind, critique conscioness and bilding identidity, to becam one spot unique to search af the social psichologist. This group cross over manifold moments and emotions are always presents, sometimesat backdrop, sometimes like figure sharped as much as named and the other to keep down, but always to come out in the discution and action. In the process our view closed relation between power and emotion somewhat to make group integrate as well as to draw up. the group to shap like the place to speech or to be quit, since the emotion like uprising and the afraid, to come out in the process to make the group one spot where the peolple shoald speak the yor problem as the place where the emotion supress too. Finilly the group don't suport the conflict and your consequence and break down to leave off a lot of achievement to community